Laparoscopic right varicocelectomy for chronic scrotal pain - Chondros, Kostas (AME Case Rep, 2018)
Varicocele represents a common problem in young men with infertility or chronic scrotal pain and it is located on the left side in the vast majority of the cases. Right isolated varicocele is a quite rare entity, especially in middle-aged men and as the single pathology responsible for chronic pain. Further investigation might be needed to exclude other retroperitoneal or scrotal hidden lesions. Several surgical options are available for symptomatic patients with clinical varicocele including the laparoscopic approach of high ligation of the spermatic veins. We present a case of a 61-year-old patient treated with laparoscopic varicocelectomy for right chronic scrotal pain.